Central Proteins of Plasma in Response to Low-Level Laser Therapy Involve in Body Hemostasis and Wound Repair: Central Proteins of Plasma in Response to Low-Level Laser Therapy - Arjmand, Babak; Vafaee, Reza; Razzaghi, Mohhamadreza; Rezaei-Tavirani, Mostafa; Ahmadzadeh, Alireza; Rezaei-Tavirani, Sina; Hamdieh, Mostafa (Journal of Lasers in Medical Sciences, 2020)
Background: Low level laser therapy (LLLT) is accompanied with protein expression change in body. There are many efforts to find the clear relationship between the differentially expressed proteins. Aim: Finding the central differentiated expressed proteins of plasma after LLLT is the aim of this study. Methods: Numbers of 6 proteins are extracted from a proteomics study and the network including these query proteins plus 100 first neighbors was constructed. The central proteins were determined based on degree value, betweenness centrality, closeness centrality, and stress. Results: Among 106 nodes of the network, 10 proteins were characterized with the most values of degree, betweenness centrality, closeness centrality, and stress. These proteins were determined as central proteins in response to LLLT in plasma. Conclusion: three query proteins; AHSG, FGG, and SERPINA1 plus seven first neighbors; FGA, ALB, KNG1, FN1, APP, TIMP1, and F5 were identified as central proteins which were dysregulated